IMPLEMENTING BUSINESS INTELLIGENCE TO IMPROVE BUSINESS PERFORMANCE - Setyaningrum, Novi Tri; Fatih, Faiz Al (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Business Intelligence (BI) has grown rapidly in recent years and has become one of the key components in business strategies to improve operational efficiency, support data-driven decision-making, and strengthen corporate competitiveness. Business Intelligence enables organizations to collect and integrate data from various sources, then analyze the data to provide deeper insights. This article aims to explore the application of Business Intelligence, its benefits, challenges faced, and practical solutions that can be implemented to maximize the potential of Business Intelligence in improving business performance. This research utilizes a systematic literature review method that covers recent studies between 2019 and 2024. The results show that the implementation of Business Intelligence can increase a company's operational efficiency, improve risk management, and enhance strategic decision-making. However, Business Intelligence implementations also face a number of challenges, such as data quality issues, as well as high initial implementation costs. The article also offers practical solutions to overcome these obstacles, including data infrastructure development, employee training, and a phased implementation approach.